Indications and outcomes of an endoscopic approach under laparotomy for the treatment of bilioenteric anastomotic strictures. (23rd December 2015) - Tokodai, Kazuaki; Kawagishi, Naoki; Miyagi, Shigehito; Nakanishi, Chikashi; Hara, Yasuyuki; Fujio, Atsushi; Kashiwadate, Toshiaki; Kanno, Atsushi; Goto, Hitoshi; Kamei, Takashi; Ohuchi, Noriaki
Abstract: BAS is a potentially life‐threatening complication of LDLT. The aim of this study was to report on the indications and outcomes of an endoscopic approach under laparotomy being used in our institution to treat BAS after LDLT, using hepaticojejunostomy, for a small case series. Eighty‐three patients underwent an LDLT in our institution between 1991 and 2014. Retrospective chart review indicated that 10 of these patients developed BAS and were included in our analysis. The endoscopic approach under laparotomy was used in three patients who developed BAS 10 yr or more after their LDLT and in whom a percutaneous transhepatic approach and an endoscopic approach had failed. The course of recovery post‐operatively was unremarkable for two of the three patients who underwent the endoscopic approach under laparotomy. One patient required follow‐up laparotomy to treat a perforation of the bowel causing acute peritonitis. At follow‐up one yr post‐operatively, the stent tube was removed in two patients who recovered fully. The other patient had full recovery with the stent remaining in situ . The endoscopic approach under laparotomy could be a safe and promising option in the treatment of BAS to avoid surgical re‐anastomosis.